(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2020)
Organizational innovation acquires a major role in improving the performance of organizations through its dimensions related to the internal environment in the organization and motivating workers, developing their creative ideas and directing their creative behavior, to increase the level of innovation in organizations, and it acquires great importance in light of the challenges posed by the continuous and accelerating changes taking place in the business environment at the time The present. Many researchers unanimously agreed on the important role of all kinds of innovation in achieving the competitive advantages of organizations, and organizational innovation is one of the most prominent and oldest types of innovation. The research aims to evaluate organizational innovation with its dimension related to the organizational climate supporting innovation in the Syrian Commercial Bank within the crisis conditions by applying the “Situational Outlook Questionnaire” SOQ scale and the research is based on two main hypotheses that have been tested by the Statistical Package for Social Sciences , SPSS V (23), and the researcher reached several results, the most important of them are: There is an average evaluation of organizational innovation indicators related to the organizational climate supporting innovation in the Commercial Bank of Syria, and there is a weak direct relationship between the organizational innovation available in the bank in question. It clarified the bank’s ability to achieve a competitive advantage within the current circumstances, and the researcher presented several proposals, the most prominent of which was creating a stimulating regulatory environment based on the challenge and commitment to achieving goals, taking risks and taking responsibility for serious decisions, and accepting the results of their application.